Single-cell transcriptome analysis reveals a cellular immune response in freshwater dark sleeper (Odontobutis potamophila) after infection with Aeromonas veronii - Liu, Guoxing; Zhu, Chenxi; Gao, Xiaojian; Zheng, You; Zhu, Xinhai; Jiang, Hucheng; Wei, Wanhong; Jiang, Qichen; Zhang, Xiaojun (Frontiers in Physiology, 2023)
The bacterium Aeromonas veronii is a co-pathogenic species that can negatively impact the health of both humans and aquatic animals. In this study, we used single-cell transcriptome analysis (scRNA-seq) to investigate the effects of infection with A. veronii on head kidney cells and the regulation of gene expression in the dark sleeper (Odontobutis potamophila). scRNA-seq was used to assess the effects of infection with A. veronii in O. potamophila B cells, endothelial cells, macrophages, and granulocytes, and differential enrichment analysis of gene expression in B cells and granulocytes was performed. The analyses revealed a significant increase in neutrophils and decrease in eosinophils in granulocytes infected with A. veronii. Activation of neutrophils enhanced ribosome biogenesis by up-regulating the expression of rps12 and rpl12 to fight against invading pathogens. Crucial pro-inflammatory mediators il1b, ighv1-4, and the major histocompatibility class II genes mhc2a and mhc2dab, which are involved in virulence processes, were up-regulated, suggesting that A. veronii activates an immune response that presents antigens and activates immunoglobulin receptors in B cells. These cellular immune responses triggered by infection with A. veronii enriched the available scRNA-seq data for teleosts, and these results are important for understanding the evolution of cellular immune defense and functional differentiation of head kidney cells.